Associations Between Race, Perceived Psychological Stress, and the Gut Microbiota in a Sample of Generally Healthy Black and White Women: A Pilot Study on the Role of Race and Perceived Psychological Stress. Issue 7 (September 2018) - Carson, Tiffany L.; Wang, Fuchenchu; Cui, Xiangqin; Jackson, Bradford E.; Van Der Pol, William J.; Lefkowitz, Elliot J.; Morrow, Casey; Baskin, Monica L.
ABSTRACT: Objective: Racial health disparities persist among black and white women for colorectal cancer. Understanding racial differences in the gut microbiota and related covariates (e.g., stress) may yield new insight into unexplained colorectal cancer disparities. Methods: Healthy non-Hispanic black or white women (age ≥19 years) provided survey data, anthropometrics, and stool samples. Fecal DNA was collected and isolated from a wipe. Polymerase chain reaction was used to amplify the V4 region of the 16SrRNA gene and 250 bases were sequenced using the MiSeq platform. Microbiome data were analyzed using QIIME. Operational taxonomic unit data were log transformed and normalized. Analyses were conducted using linear models in R Package "limma." Results: Fecal samples were analyzed for 80 women (M (SD) age = 39.9 (14.0) years, 47 black, 33 white). Blacks had greater average body mass index (33.3 versus 27.5 kg/m 2, p < .01) and waist circumference (98.3 versus 86.6 cm, p = .003) than whites. Whites reported more stressful life events ( p = .026) and greater distress ( p = .052) than blacks. Final models accounted for these differences. There were no significant differences in dietary variables. Unadjusted comparisons revealed no racial differences in alpha diversity. Racial differences were observed in beta diversity and abundance of top 10 operational taxonomic units. Blacks had higher abundances than whites of Faecalibacterium ( p = .034) and Bacteroides ( p = .038). Stress was associated with abundances of Bifidobacterium. The association between race and Bacteroides (logFC = 1.72, 0 = 0.020) persisted in fully adjusted models. Conclusions: Racial differences in the gut microbiota were observed including higher Bacteroides among blacks. Efforts to cultivate an "ideal" gut microbiota may help reduce colorectal cancer risk. Abstract : Supplemental digital content is available in the text.